The days Argentina stood still. History, nation and imaginable futures in the public interpretations of the Argentine crisis at the beginning of the twenty-first century - Visacovsky, Sergio Eduardo (2018)
This article is focused on public interpretations of the Argentine ?crisis? at the beginning of the twenty-fi rst century as necessary conditions for the constitution of the event. Such interpretations held that Argentina was dominated by a kind of evil force originated a long time ago, but whose eff ects persisted in the present. And, unless it was conjured once and for all, it would remain active and damaging in the future.Thus, the ?crisis? was seen as an episode of the continuous failures. Based on opinion pieces or leading articles in newspapers and general interest and political magazines,academic articles and books, I want to show how the imagination of possible futures depended on the conceptions of temporalities implicit in the interpretations embedded in narratives and diff erent valuations of events, fi gures and ideas. These gave historical specificity to the event and led to the emergence of new scenarios for political action.